Angiocentric Glioma: The Infiltrative Glioma with Ependymal Differentiation - Ayca ERSEN; M. Serefettin CANDA; Suleyman MEN; Kemal YUCESOY; Orhan KALEMCI; Tulay CANDA (Federation of Turkish Pathology Societies, 2017)
Angiocentric glioma is an epileptogenic, infiltrative, low grade glial tumor, with ependymal and astrocytic differentiation, most commonly seen in young adults and the pediatric age group. Herein we report a case of 21-year-old male patient who presented with fever and pharmaco-resistant seizures. Computed tomography revealed an iso-dense mass lesion in the gyrus rectus of the left frontal lobe. On magnetic resonance imaging the mass was hyperintense on both T1- and T2-weighted images with no contrast enhancement. Histopathological examination revealed monomorphous tumor cells diffusely infiltrating the neuropil with circumferential, radial, or longitudinal angiocentric alignment and subpial aggregation with perpendicular alignment of the cells to the pial surface. Among central nervous system tumors with ependymal differentiation, this distinct entity is the one with an infiltrating growth pattern. In spite of the infiltrating pattern, it does not seem to have a potential for aggressive behavior.